IMPLEMENTASI PERATURAN KOMISI PEMILIHAN UMUM NOMOR 15 TAHUN 2013 TENTANG PEMASANGAN ATRIBUT KAMPANYE CALON LEGISLATIF DI KOTA SAMARINDA - Afriansyah Afriansyah (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTSamarinda City Government already shaping urban spatial structure which is still under construction, seen from the city parks that have been built.Samarinda City Government is supposed to be more assertive in dealing with all forms of spatial planning in the City because the City Government of Samarinda Samarinda considered most responsible for the problem. Towards the Year of Political or Party Democracy General Election in 2014, various kinds of attributes Campaign has begun to adorn public places in the city of Samarinda.Hence the rise of Installation Attributes of Political Parties and Candidates Campaign Legislature is not in place will make arrangements Samarinda city is increasingly becoming damaged due to a variety of interests, in which the pursuit of Professional Political Political Party as a vehicle to make their career.Installation of Executive Viewer Tool Campaign by Campaign done by considering ethics, aesthetics, cleanliness and beauty of the city or local area in accordance with the legislation in force. Installation Viewer tool that is installed is not in place would have been in violation of Article 17 Paragraph 1 Clause (a) PKPU Number 15 Year 2013, which confirms that the installation Props shall not be placed in a place of Worship, hospitals or places of Health Services, Government Owned Buildings, institutions, main streets, and highways. In PKPU No. 15 of 2013 Article 17 Paragraph 1 Clause (b) also mentioned that participants in the election that any political party can only put up a billboard or advertisement boards in every village in the zones that have been established or agreed upon. Efforts KPU Samarinda in the discipline attribute has a maximum Legislative Candidates Campaign implemented, in this case the Commission and the Election Supervisory Committee Samarinda City in collaboration with Civil Service Police Unit (municipal police) as the executor from the field in order to curb Props are not installed in place. Based on the interview with the author of Samarinda City Commission and the Election Supervisory Committee stated that all Political Parties and Legislative Candidates in the city of Samarinda do Violations Installation Attributes Campaign.